Impact assessment of frontline demonstrations on mustard (Brassica juncea L.) under North Gujarat agro-climatic region: IMPACT ASSESSMENT OF FRONTLINE DEMONSTRATIONS ON MUSTARD UNDER GUJARAT - A L JAT; K P PRAJAPATI; J R PATEL; A G DESAI (Journal of Oilseeds Research, 2020)
Rapeseed-mustard is an important oilseed crop of India, but its productivity is low due to lack of awareness about improved varieties, production and protection technologies. Castor-Mustard Research Station, S.D. Agricultural University, Sardarkrushinagar, Gujarat conducted 87 Frontline Demonstrations in the farmer’s fields on mustard varietyGDM 4 and NRCHB 101 over three consecutive years during rabi seasons of 2015-16 to 2017-18 under North Gujarat Agroclimatic region. The results revealed that mustard varieties GDM 4 and NRCHB 101 out yielded by 17.2% and 16.1% over local farmers’ practices based on three years average yield performance. Furthermore, the mustard variety GDM 4 and NRCHB 101 recorded higher B:C ratio with the mean value of 3.58 and 3.53 as well as higher additional net monetary returns of ` 11289 and 10311 per ha over farmers’ practices.